PENGARUH KEADILAN PROSEDUR EVALUASI TERHADAP ORGANIZATIONAL COMMITMENT DIMEDIASI OLEH KEADILAN DISTRIBUTIF, KEPUASAN KERJA DAN KEPERCAYAAN PADA ATASAN - Syahnasthalia Syahnasthalia; Ria Nelly Sari; Rheny Afriana Hanif (Department of Accounting-Faculty of Economic and Business (FEB), 2015)
This study aimed to determine (1) the indirect effect of fairness of evaluationprocedure on job satisfaction through distributive fairness and trust in superior and Thisstudy used the online survey method by sending a questionnaire via email using GoogleForms. The sample was mid-level managers in companies listed on the Indonesia StockExchange. Hypothesis testing conducted on 65 responses can be processed. Analysis of datausing the approach SEM. The results show that (1) job satisfaction is able to mediate the effectof fairness of evaluation procedure on job satisfaction, (2) distributive fairness is able tomediate the effect of fairness of evaluation procedures on organizational commitment, and (3)job satisfaction is able to mediate the effect fairness of evaluation procedures onorganizational commitment. This study couldn’t prove that (1) distributive fairness mediatesthe effect of fairness of evaluation procedures on job satisfaction, (2) trust in superiormediates the effect of fairness of evaluation procedures on organizational commitmentDOI: 10.15408/akt.v8i3.2773